Motion Graphic Design on Safe Boundaries of Digital Relations and Child Grooming in Teenagers - Alifah Khoirunnisa; Rahina Nugrahani; Yasser Awaluddin (fakultas Desain Komunikasi Visual, 2026)
The rapid development of social media among adolescents has increased the risk of digital exploitation, including child grooming practices. Lack of understanding of safe boundaries in digital relationships means that many adolescents are unable to recognize emotional manipulation, excessive attention patterns, and the risks of sharing personal information on social media. This study aims to design an educational motion graphic about safe boundaries in digital relationships and child grooming among adolescents as a digital education campaign medium. The method used is Design Thinking, which includes the stages of empathize, define, ideate, prototype, and test. Data collection was carried out through observation, literature review, and analysis of references related to adolescent digital behavior and the issue of online exploitation. The results of the study are educational motion graphics in vertical video format that combine digital illustrations, typography, animation, audio narration, and a storytelling approach to convey messages in a communicative and engaging manner. The visual concept uses a children's cartoon illustration style with a dominant purple color. The designed motion graphic was then used by the Anantaka Foundation as a digital education campaign medium through Instagram. This media is expected to increase adolescent awareness of the importance of maintaining safe boundaries in digital relationships and recognizing the risks of child grooming.